Mathematical Self-Evaluation of Grade 4 and 8 Pupils - Smetáčková, Irena (Scientia in educatione, 2016)
The accuracy of self-evaluation is part of meta-cognition. It supports the efficiency of learning process. The article presents the study on an accuracy estimation in mathematics achievements for 4th and 8th grade pupils. The influence of age, gender, test score, mark from mathematics and mathematics self-efficacy is considered. The study found a slight tendency to overvalue mathematics achievement both in younger and older group. In adolescence the gender difference exists with a tendency to overvalue by boys and undervalue by girls.